2013
DOI: 10.1136/medethics-2012-101286
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of a simplified assent form in a vaccine trial for adolescents: Table 1

Abstract: Introduction Future HIV vaccine efficacy trials with adolescents will need to ensure that participants comprehend study concepts in order to confer true informed assent. A Hepatitis B vaccine trial with adolescents offers valuable opportunity to test youth understanding of vaccine trial requirements in general. Methods Youth reviewed a simplified assent form with study investigators and then completed a comprehension questionnaire. Once enrolled, all youth were tested for HIV and confirmed to be HIV-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Studies show that this process has been insufficient to achieve its ethical goal, since children and adolescents do not understand a great deal of the information about the research in which they are involved 4,[12][13][14][15] . In this sense, obtaining the FPIC from these participants may represent failure of the principle of respect for people 16 , because it only formally fulfills the ethical determination to provide participants with information and clarification about the study.…”
Section: Children's Knowledge Of the Terms Of Informed Assentmentioning
confidence: 99%
“…Studies show that this process has been insufficient to achieve its ethical goal, since children and adolescents do not understand a great deal of the information about the research in which they are involved 4,[12][13][14][15] . In this sense, obtaining the FPIC from these participants may represent failure of the principle of respect for people 16 , because it only formally fulfills the ethical determination to provide participants with information and clarification about the study.…”
Section: Children's Knowledge Of the Terms Of Informed Assentmentioning
confidence: 99%
“…Instead, they only stated that the highest portion of participants that answered all questions correctly was in the story group [11]. Three additional studies found that using everyday language with graphs and Q&A format, an illustrated booklet, and a comic strip in the assent process generally led to good understanding of the research details, but the interventions were not tested against a standard or control format [16,18,20].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Lee et al [7] investigated how youths comprehend an assent form in the setting of a Hepatitis B vaccine trial. One hundred and twenty three adolescents 12-17 years of age (average age was 15 years) read a consent form and completed a comprehension test.…”
Section: Measuring Children's Capacity To Consent To Researchmentioning
confidence: 99%
“…The percentage of subjects who demonstrated absolute comprehension (100 % correct answers) was 56 %. This may imply that had they been asked to make a decision, almost half would have based their decision on information they did not fully understand [7].…”
Section: Measuring Children's Capacity To Consent To Researchmentioning
confidence: 99%